ANALISIS PERBEDAAN KADAR KAFEIN PADA KOPI BUBUK HITAM DAN KOPI BUBUK PUTIH INSTAN SECARA SPEKTROFOTOMETRI UV-Vis. - Nur Patria Tjahjani; Afra Chairunnisa; Hana Handayani (STIKES Cendekia Utama Kudus, 2021)
Coffee is famous for its high caffeine content, with the main role of caffeine in the body is to improve psychomotor work so that the body stays awake and provides a physiological effect in the form of increased energy with a limit on coffee consumption of no more than 3-4 cups of coffee a day. Caffeine is a type of xanthine alkaloid that has two carbon rings with four nitrogen atoms and has a bitter taste. This study aims to determine the caffeine levels in black ground coffee and white ground coffee, analyze the differences and to find out the theoretical caffeine levels in one cup of coffee. The method used for qualitative analysis using UV- Vis Spectrophotometer at wavelength of 273 nm, the experiment was carried out three times the replication. The results of the study of caffeine content in black coffee powder samples and instant white coffee powder in a row were : H1 4,8mg: H2 3,65 mg; H3 4,85 mg; H4 3,95 mg; H5 3,85 mg; P1 9,85 mg; P2 8,8 mg; P3 9,6 mg; P4 7,4 mg; P5 6,45 mg. T tests results showed significant differences in caffeine levels of black ground coffee and white ground coffee with a value of p=0,00. According to the Indonesian Pharmacopoeia (1995), if it is theoretically reviewed in one consumption / sachet of black powdered coffee and instant white powdered coffee is still within reasonable limits or does not exceed the usual dose, which is 300 -600 mg.